Effects of Mangifera indica (Careless) on Microcirculation and Glucose Metabolism in Healthy Volunteers - Buchwald-Werner, Sybille; Schön, Christiane; Frank, Sonja; Reule, Claudia (Planta Medica, 2017)
A commercial Mangifera indica fruit powder (Careless) showed beneficial acute effects on microcirculation in a randomized, double-blind, crossover pilot study. Here, long-term effects on microcirculation and glucose metabolism were investigated in a double-blind, randomized, placebo-controlled, 3-arm parallel-design study in healthy individuals. A daily dose of 100 mg or 300 mg of the fruit powder was compared to placebo after supplementation for 4 weeks. Microcirculation and endothelial function were assessed by the Oxygen-to-see System and pulse amplitude tonometry, respectively. Glucose metabolism was assessed under fasting and postprandial conditions by capillary glucose and HbA1c values.Microcirculatory reactive hyperemia flow increased, especially in the 100 mg group (p = 0.025). The 300 mg of the M. indica fruit preparation reduced postprandial glucose levels by trend if compared to placebo (p = 0.0535) accompanied by significantly lower HbA1c values compared to baseline. Furthermore, 300 mg intake significantly improved postprandial endothelial function in individuals with decreased endothelial function after high-dose glucose intake (p = 0.0408; n = 11).In conclusion, the study suggests moderate beneficial effects of M. indica fruit preparation on microcirculation, endothelial function, and glucose metabolism.
Keywords: Mangifera indica; Anacardiaceae; Careless; microcirculation; endothelial function; glucose metabolism; human study